1998
DOI: 10.2307/3870664
|View full text |Cite
|
Sign up to set email alerts
|

The Sex-Inducing Pheromone and Wounding Trigger the Same Set of Genes in the Multicellular Green Alga Volvox

Abstract: The sex-inducing pheromone of the multicellular green alga Volvox carteri is a glycoprotein that triggers development of males and females at a concentration <10(-16) M. By differential screening of a cDNA library, two novel genes were identified that are transcribed under the control of this pheromone. Unexpectedly, one gene product was characterized as a lysozyme/chitinase, and the other gene product was shown to encode a polypeptide with a striking modular composition. This polypeptide has a cysteine protea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Wounding Induces Transcription of dz-hrgp Gene-As demonstrated recently (18), all genes known so far to be under the control of the sex-inducing pheromone are also triggered by wounding. This observation led us to investigate whether transcription of dz-hrgp gene is also responsive to wounding.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…Wounding Induces Transcription of dz-hrgp Gene-As demonstrated recently (18), all genes known so far to be under the control of the sex-inducing pheromone are also triggered by wounding. This observation led us to investigate whether transcription of dz-hrgp gene is also responsive to wounding.…”
Section: Resultsmentioning
confidence: 81%
“…Surprisingly, the simple multicellular green alga Volvox responds to wounding in much the same way as observed in higher plants. As was demonstrated recently (18), Volvox responds to wounding with the synthesis of a chitinase as well as a protease that is combined with chitin-binding modules. With the additional demonstration of a typical HRGP that is produced in response to wounding, it now appears that much of the response scenario found in higher plants already exists in multicellular green algae.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The effect of this unique sequence on protease function is currently unknown. In addition, the amino acid sequence from position 188 to 236 has approximately 70% similarity to the chitin-binding domains present in a Volvox cysteine protease (11), wheat germ agglutinin (12,13), and hevein (14,15), and recent experiments confirmed that the 33-kDa cysteine protease has chitin-binding activity (unpublished data). mir1 has been mapped to chromosome 6 (bin 6.02) on the maize genome, where there is a significant quantitative trait locus for resistance to European corn borer leaf feeding (16).…”
mentioning
confidence: 81%